The death of security sector reform? The South African exemplar revisited. Issue 2 (4th March 2019) - Cawthra, Gavin
ABSTRACT: Security sector reform (SSR) or transformation in South Africa has until recently almost universally been regarded as a success. While achievements have been real and many are enduring, under the presidency of Jacob Zuma a creeping effort by corrupt parvenu elites to capture the state for personal enrichment has become evident. The impact of this on the SSR project has not been sufficiently analysed. This article does not deal with state capture per se, which would be massive task and for which evidence is still emerging. It limits itself to the impact of state capture on the SSR project, examining the hollowing out of the defence function, as well as the corruption and factional politicisation of the intelligence, policing and prosecutions functions (it does not deal with the capture of state-owned enterprises, which would require a study in its own right). It concludes that SSR has been significantly undermined. The question is asked whether a resurrection is possible or desirable.